2016
DOI: 10.1002/adma.201505403
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Polarized Biomaterials

Abstract: Electrically polarized biomaterials and their interactions with the surrounding biological environment is important for understanding the host response, growth and inhibition of biological species as well as the long-term fate and performance of the implants. Polarized materials possess electrical charges at the surface due to polar or electret properties. As these surfaces are at the frontier of biological reactions understanding biological interactions at the interface with polarized biomaterials requires a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 99 publications
0
50
0
Order By: Relevance
“…Thus, they can be used to mimic the bone's ability to generate electrical potentials under a mechanical load without the need for an external power source. Piezoelectric ceramics as bone replacement materials are currently not used in implant devices; however, in vitro studies indicate improved biocompatibility and bone‐inductive ability on piezoelectric ceramic surfaces (Bodhak, Bose, & Bandyopadhyay, ; Tofail & Bauer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they can be used to mimic the bone's ability to generate electrical potentials under a mechanical load without the need for an external power source. Piezoelectric ceramics as bone replacement materials are currently not used in implant devices; however, in vitro studies indicate improved biocompatibility and bone‐inductive ability on piezoelectric ceramic surfaces (Bodhak, Bose, & Bandyopadhyay, ; Tofail & Bauer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Surface electrical charges in biomaterials have also been recognized as an important parameter that determines cell activity . This is a result of cellular endogenous electrical and transmembrane voltage potentials . For electroactive biomaterials, such as piezoelectrics, the terms “smart biomaterials” or “the fourth generation of biomaterials” have been coined.…”
Section: Introductionmentioning
confidence: 99%
“…They feature extremely high piezoelectricity and sensing capabilities rendering that application of an electric field or mechanical load can be used for tuning their surface electrical charges. Thus, due to their surface electrical charges and piezoelectricity, they can interact with cells electrically or via nanoscale mechanical stimulation . Ferroelectrics neither require external power sources to manifest surface electric charges, nor electrodes, which is a clear advantage over other electroactive materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes disruption in the wound biofilm and promotes wound healing. It has been reported that direct electrical stimulation of wound surfaces can regulate various factors involved in the overall wound healing process, including promoting angiogenesis, increasing direct cell migration to the wound site, and decreasing edema . Use of direct current (DC) has been reported as the most common and efficient method for electrical stimulation of wound healing.…”
mentioning
confidence: 99%